Control and responsibility in the implementation of management decisions in government bodies ("Journal "U". Economy. Management. Finance.", 2023)
The article analyzes the features of the implementation of managerial decisions in government bodies in terms of the control and responsibility function; reveals the essence of managerial decision-making in government structures, the conditionality of the regulatory framework, comprehensive objectivity and validity; highlights criteria for evaluating the effectiveness of managerial decision execution; determines the sequence of control measures in government.
Keywords: activity of authorities; management decision; control; responsibility; civil society; public service